Direct oral anticoagulants and antiplatelet agents - Sibbing, D.; Spannagl, M. (Hämostaseologie, 2014)
Oral anticoagulants and platelet receptor blockers are widely used in clinical practice with the aim of reducing the risk of thrombotic complications in patients with cardiovascular diseases. Their regular intake and adequate antithrombotic action is vital and this is way numerous assays have been developed for laboratory testing and monitoring of these agents. Available assays can be stratified into pharmacokinetic and pharmacodynamic assays. Such assays are increasingly used in clinical routine and their daily use is triggered by the advent of the novel direct oral anticoagulants (DOACs) as an alternative for vitamin K antagonist (VKA) treatment, which are dabigatran, rivaroxaban and apixaban, and by the advent of prasugrel or ticagrelor as an alternative for clopidogrel with regard to platelet P2Y12 receptor inhibition.In this review the most important and most commonly used laboratory assays are summarized as well as their clinical implications with the focus on DOACs as an alternative for VKAs and the different P2Y12 receptor blockers for ant-iplatelet treatment.
Keywords: Oral anticoagulation; platelet aggregation; drug monitoring